Inspiring Leadership and Its Role in Boosting Organizational Quality Analytic Study at the Iraqi Islamic Bank for Investment and Development - ALBayati, Mohammed Thaer Ali (Indonesian Journal of Law and Economics Review, 2026)
General Background: Leadership plays a critical role in organizational performance and the ability of institutions to adapt to dynamic environments. Specific Background: Inspiring leadership, characterized by future vision, self-confidence, change management, and employee empowerment, is increasingly associated with the development of organizational quality. Knowledge Gap: However, empirical evidence explaining how these leadership dimensions relate to organizational quality in Islamic banking institutions remains limited. Aims: This study analyzes the relationship between inspiring leadership and organizational quality at the Iraqi Islamic Bank for Investment and Development. Results: Using data from 279 employees and applying descriptive statistics, simple linear regression, and stepwise regression, the findings reveal a significant positive relationship between inspiring leadership and organizational quality, explaining about 53.1% of its variance. Self-confidence, future vision, and change management emerge as the most prominent determinants, while employee empowerment shows limited statistical contribution. Novelty: The study provides empirical evidence regarding the relative importance of inspiring leadership dimensions in explaining organizational quality within an Islamic banking context. Implications: The findings suggest that strengthening leaders’ confidence, clarifying future vision, and improving change management practices can support the development of organizational quality in banking institutions. Highlights: • Leadership Self-Confidence Emerges as the Strongest Determinant of Institutional Quality Variation. • Strategic Vision and Structured Change Practices Jointly Strengthen Internal Performance Conditions. • Staff Autonomy Mechanisms Show Limited Statistical Contribution Within the Examined Banking Context. Keywords: Inspiring Leadership, Organizational Quality, Islamic Banking, Leadership Self-Confidence, Change Management.